2011
DOI: 10.1099/vir.0.033662-0
|View full text |Cite
|
Sign up to set email alerts
|

High rate of viral evolution in the capsid protein of porcine parvovirus

Abstract: In recent years, it has been shown that some parvoviruses exhibit high substitution rates, close to those of RNA viruses. In order to monitor and determine new mutations in porcine parvovirus (PPV), recent PPV field isolates from Austria, Brazil, Germany and Switzerland were sequenced and analysed. These samples, together with sequences retrieved from GenBank, were included in three datasets, consisting of the complete NS1 and VP1 genes and a partial VP1 gene. For each dataset, the nucleotide substitution rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
49
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 30 publications
6
49
0
3
Order By: Relevance
“…Porcine parvovirus infection is highly prevalent in domestic pigs (Sus scrofa) in Brazil and is considered to be the main cause of reproductive problems in herds (Streck et al 2011). Domestic pigs were introduced to the Pantanal 200 years ago and became feral during the Paraguay War.…”
Section: Discussionmentioning
confidence: 99%
“…Porcine parvovirus infection is highly prevalent in domestic pigs (Sus scrofa) in Brazil and is considered to be the main cause of reproductive problems in herds (Streck et al 2011). Domestic pigs were introduced to the Pantanal 200 years ago and became feral during the Paraguay War.…”
Section: Discussionmentioning
confidence: 99%
“…If the fetuses are infected after day 70 of gestation, they usually develop antibodies against PPV and eliminate the virus (Zeeuw et al, 2007;Truyen & Streck, 2012). In recent years, studies have shown that PPV is much more diverse than previously thought (Zimmermann et al 2006;Streck et al, 2011). Several PPV strains of different virulence are known.…”
mentioning
confidence: 99%
“…Based on phylogenetic analyses of the VP1/VP2 protein genes, PPV can be defined into at least seven clusters (Zimmermann et al, 2006;Streck et al, 2011Streck et al, , 2013a. Recently, a population dynamic analysis showed that, despite the high evolutionary rate, only a few PPV strains (similar to strain 27a) have been predominant in Europe in recent years (Streck et al, 2013b).…”
mentioning
confidence: 99%
“…This results in the constant presence of PPV in herds, enabling the occurrence of mutated field strains. This virus has a single-stranded DNA (ssDNA) genome, known to have a high mutation rate (8). Monitoring the emergence of new strains and understanding cell-virus interactions are therefore important to gain a better knowledge of the life cycle of this pathogen.…”
mentioning
confidence: 99%